Hardfacing of duplex stainless steel using melting and diffusion processes - H, Lailatul; Maleque, Md. Abdul (IOP Publishing, 2017)
Duplex stainless steel (DSS) is a material with high potential successes in many new applications such as rail car manufacturing, automotive and chemical industries. Although DSS is widely used in various industries, this material has faced wear and hardness problems which obstruct a wider capability of this material and causes problems in current application. Therefore, development of surface modification has been introduced to produce hard protective layer or coating on DSS. The main aim of this work is to brief review on hard surface layer formation on DSS using melting and diffusion processes. Melting technique using tungsten inert gas (TIG) torch and diffusion technique using gas nitriding are the effective process to meet this requirement. The processing route plays a significant role in developing the hard surface layer for any application with effective cost and environmental factors. The good understanding and careful selection of processing route to form products are very important factors to decide the suitable techniques for surface engineering treatment. In this paper, an attempt is also made to consolidate the important research works done on melting and diffusion techniques of DSS in the past. The advantages and disadvantages between melting and diffusion technique are presented for better understanding on the feasibility of hard surface formation on DSS. Finally, it can be concluded that this work will open an avenue for further research on the application of the suitable process for hard surface formation on DSS.